Targeting Orai1-Mediated Store-Operated Ca2+ Entry in Heart Failure - Luo, Rui; Gomez, Ana-Maria; Benitah, Jean-Pierre; Sabourin, Jessica (Frontiers in Cell and Developmental Biology, 2020)
The archetypal store-operated Ca2+ channels (SOCs), Orai1, which are stimulated by the endo/sarcoplasmic reticulum (ER/SR) Ca2+ sensor stromal interaction molecule 1 (STIM1) upon Ca2+ store depletion is traditionally viewed as instrumental for the function of non-excitable cells. In the recent years, expression and function of Orai1 have gained recognition in excitable cardiomyocytes, albeit controversial. Even if its cardiac physiological role in adult is still elusive and needs to be clarified, Orai1 contribution in cardiac diseases such as cardiac hypertrophy and heart failure (HF) is increasingly recognized. The present review surveys our current arising knowledge on the new role of Orai1 channels in the heart and debates on its participation to cardiac hypertrophy and HF.